AB0605 SERUM NEOPTERIN AND ISCHEMIA MODIFIED ALBUMIN LEVELS ARE ASSOCIATED WITH THE DISEASE ACTIVITY OF ADULT IMMUNOGLOBULIN A VASCULITIS (HENOCH-SCHONLEIN PURPURA). (June 2019) - Omma, Ahmet; Colak, Seda; Sandikci, Sevinc Can; Yucel, Cigdem; Erden, Abdulsamet; Sertoglu, Erdim; Özgürtaş, Taner
Abstract : Background: Immunoglobulin a vasculitis (IgAV) [formerly called Henoch– Schönlein purpura (HSP)] is an IgA mediated systemic vasculitis which primarily affects skin, gastrointestinal system and small vessels of kidneys. Exact pathogenesis of IgAV remains unknown. A fewclinicalstudiesevaluatedthe role of oxidativeinjury in thepathogenesis of vasculitis. Ischemia modified albumine (IMA) and Neopterin increased status of oxidative stress. Objectives: The aims of the study are to investigate serum neopterin and IMA levels in patients with IgAV and evaluate the association of these markers with disease activity and relapse. Methods: Thirty-four consecutive adult patients (24 males and 10 females) admitted to the rheumatology clinic of ankara Numune Training and Research Hospital meeting the IgAVAmerican College of Rheumatology (ACR) criteria were enrolled in this cross-sectional study. Demographic and clinical features of IgAV and control group were recorded into a predefined protocol. Disease activity was categorized as "remission" or "active" according to BVAS. BVAS ≥1 was accepted "active".Serum neopterin levels, hsCRP and IMA were evaluated according to BVAS and compared to healthy control group. Results: Serum median (IQR) neopterin, IMA levelsandhsCRPwerehigher in thestudygroupthan in controlgroup [2.01 (12.5) ng/mL vs. 1.77 (1.37) ng/mL, 0.67 (0.2) ng/mL vs. 0.43 (0.17) ng/mL, 5.6 (17.1) mg/L vs. 1.55 (1.6) mg/L, p=0.095, p<0.001and p=0.002, respectively). When evaluated according to BVAS, IMA and hsCRP levels were significantly higher in the group with active disease [0.77 (0.12) vs. 0.61 (0.13) and 14.85 (4.6), p=0.009 and p=0.03, respectively]. Serum neopterin levels were significantly higher in the active group compared to BVAS [18.95 (32.36) vs. 1.63 (1.48), p<0.001]. Conclusion: Oxidative stress is important in HSP pathogenesis. Roles of hsCRP, Neopterin and IMA as potential markers of diagnosis and disease activity seem to be worth studying in the future studies with larger study groups. Disclosure of interests: None declared